PENGARUH IMPLEMENTASI GREEN BANKING TERHADAP PROFITABILITAS PADA SEKTOR PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2021-2024 - Helmi Romadhon; Ernie Hendrawaty; Fajrin Satria Dwi Kesumah (Nusantara Hasana Journal, 2026)
This study aims to analyze and examine the effect of green banking implementation using the Green Coin Rating (GCR) approach and Automated Teller Machines (ATM) as a form of green banking implementation in banking products and services on profitability, as measured by Return on Assets (ROA). This study also incorporates bank-specific factors, namely Non-Performing Loans (NPL), Operating Expenses to Operating Income (BOPO), and Loan to Deposit Ratio (LDR), as well as macroeconomic factors such as inflation and Gross Domestic Product (GDP) as control variables in the banking sector listed on the Indonesia Stock Exchange during the 2021–2024 period. The population of this study consists of 47 banking companies, with 36 companies selected as samples using purposive sampling. The data were analyzed using multiple linear regression with panel data through EViews 12 software. The results show that green banking, as measured by GCR, does not have a significant effect on profitability. In addition, the number of ATMs also does not significantly affect profitability.